Integrated Marketing Communication for BPJS Ketenagakerjaan: Understanding Communication Design and Channel to Improve Membership Ratio Among Indonesian Migrant Workers - Hisyam, Abdullah; Silas Mussry, Jacob (Journal of Accounting and Finance Management, 2025)
The number of Indonesian Migrant Workers continue to increase due to increasing demand for workforce needs from various countries. In accordance with the mandate of Law of the Republic of Indonesia Number 18 of 2017, BPJS Ketenagakerjaan must expands its role to Migrant Worker. However, the suboptimal participation level of Indonesian migrant workers still become one of the main issue. With membership ratio stands at 12.6%, indicating that there is still a gap between BPJS Ketenagakerjaan services and its awareness. This study aims to formulate prioritization for integrated marketing communications channel and design that is relevant for BPJS Ketenagakerjaan in reaching migrant workers. Data was collected using a quantitative method with surveys and analyzed using a weighted scoring method. The respondents consisted of Indonesian migrant workers in key destination countries such as Malaysia, Hong Kong, Taiwan, South Korea, and Japan. Research findings show that social media and community events are the most relevance communication channels. Additionally, in the aspect of communication design, research found that collaboration with trusted institutions and the marketing communication based on benefits and user experience are relevant. Meanwhile, communication activities such as billboards, direct marketing and collaboration with influencers have lower relevance.